Motivation and Satisfaction of Employees in the Workplace: A Case of Nepalese Commercial Banks - Patel, Shreeram Kumar (Nepalese Journal of Economics, 2025)
This study examines the motivation and satisfaction of employees in the workplace: A case of Nepalese commercial banks. Employee motivation and job satisfaction are the dependent variables. The selected independent variables are salary, working environment, training and development, job security, and performance appraisal. The primary source of data is used to assess the opinions of respondents regarding salary, working environment, training and development, job security, performance appraisal, employee motivation, and job satisfaction. The study is based on primary data of 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of motivation and satisfaction of employees in the workplace: A case of Nepalese commercial banks. The study showed a positive impact of salary on employee motivation and job satisfaction. It indicates that higher the salary, higher would be the employee motivation and job satisfaction. Similarly, the study showed a positive impact of working environment on employee motivation and job satisfaction. It indicates that positive working environment leads to increase in employee motivation and job satisfaction. The study also revealed a positive impact of training and development on employee motivation and job satisfaction. It indicates that higher the training and development programs, higher would be the employee motivation and job satisfaction. Likewise, the study observed a positive impact of job security on employee motivation and job satisfaction. It indicates that higher the job security, higher would be the employee motivation and job satisfaction. Similarly, the study observed a positive impact of performance appraisals on employee motivation and job satisfaction. It indicates that fair performance appraisal leads to increase in employee motivation and job satisfaction.